Activation of Checkpoint Kinase 2 by 3,3′-Diindolylmethane Is Required for Causing G(2)/M Cell Cycle Arrest in Human Ovarian Cancer Cells - Kandala, Prabodh K. (The American Society for Pharmacology and Experimental Therapeutics, 2010)
We evaluated the effect of 3,3′-diindolylmethane (DIM) in ovarian cancer cells. DIM treatment inhibited the growth of SKOV-3, TOV-21G, and OVCAR-3 ovarian cancer cells in both a dose- and time-dependent manner with effective concentrations ranging from 40 to 100 μM. Growth-inhibitory effects of DIM were mediated by cell cycle arrest in G(2)/M phase in all the three cell lines. G(2)/M arrest was associated with DNA damage as indicated by phosphorylation of H(2)A.X at Ser139 and activation of checkpoint kinase 2 (Chk2) in all the three cell lines. Other G(2)/M regulatory molecules such as Cdc25C, Cdk1, cyclin B1 were down-regulated by DIM. Cycloheximide or Chk2 inhibitor pretreatment abrogated not only activation of Chk2 but also G(2)/M arrest and apoptosis mediated by DIM. To further establish the involvement of Chk2 in DIM-mediated G(2)/M arrest, cells were transfected with dominant-negative Chk2 (DN-Chk2). Blocking Chk2 activation by DN-Chk2 completely protected cells from DIM-mediated G(2)/M arrest. These results were further confirmed in Chk2 knockout DT40 lymphoma cells, in which DIM failed to cause cell cycle arrest. These results clearly indicate the requirement of Chk2 activation to cause G(2)/M arrest by DIM in ovarian cancer cells. Moreover, blocking Chk2 activation also abrogates the apoptosis-inducing effects of DIM. Furthermore, our results show that DIM treatment cause ROS generation. Blocking ROS generation by N-acetyl cysteine protects the cells from DIM-mediated G(2)/M arrest and apoptosis. Our results establish Chk2 as a potent molecular target of DIM in ovarian cancer cells and provide the rationale for further clinical investigation of DIM.